Effect of temperature, concentration of alcohols and time on baker’s yeast permeabilization process - Trawczyńska, Ilona; Miłek, Justyna; Kwiatkowska-Marks, Sylwia (Technical Sciences, 2018)
Baker’s yeast beyond the traditional use in the food industry may be used to carry out biotransformations. The effectiveness of yeast as biocatalysts is based on the presence of large amounts of intracellular enzymes, whose efficiency can be repeatedly increased by permeabilization. It is the process of increasing the permeability of cell walls and membranes in order to facilitate reagents access to the intracellular enzyme. Alcohols permeabilization process allows for approx. 50-fold increase in catalase activity of baker’s yeast. In this paper, the influence of physical and chemical parameters on the effectiveness of permeabilization of baker’s yeast cells using alcohols was analyzed. Research has shown that with increasing temperature of permeabilization process better results are achieved using a lower alcohol concentration. Based on presented response surface graphs, we can also indicate a negligible impact of duration time on the process efficiency.